Bioinspired high toughness graphene/ZrB2 hybrid composites with hierarchical architectures spanning several length scales. (October 2016) - An, Yumin; Han, Jiecai; Zhang, Xinghong; Han, Wenbo; Cheng, Yehong; Hu, Ping; Zhao, Guangdong
Abstract: Natural bioinspired hierarchically ordered architectures from the nanoscale to the macroscale are achieved in graphene/ZrB2 hybrid composites to improve their toughness using graphene oxide. Two types of films containing different volumes of graphene oxide are self-assembled with ZrB2 or SiC micro particles through a vacuum-assisted filtration method. Scanning electron microscopy images show that ceramic particles are homogeneously distributed in a continuous multilayer graphene oxide network, forming a nano-micro hierarchical structure. Tensile tests are employed to test the strength of these films. The spark plasma sintering method is utilized to construct micro-macro structural order through densifying two types of alternately stacked films containing different volumes of graphene oxide. Indentation tests reveal alternately compressive and tensile layers are achieved after the sintering process. By combining different structural features spanning several length scales, the composites exhibit a unique combination of high strength (522 MPa) and toughness (9.5 MPa m 0.5 ); in particular, the fracture toughness is more than double that of the composite without the hierarchical architecture. The toughening mechanisms are also analyzed at different length scales. This bioinspired material-independent approach should be employed in the designing and processing of materials for structural, high-temperature and energy related applications.